Understanding bank-run contagion - Martin Brown; Stefan T. Trautmann; Razvan Vlahu (European Central Bank (ECB), 2014)
We study experimental coordination games to examine through which transmission channels, and under which information conditions, a panic-based depositor-run at one bank may trigger a panic-based depositor-run at another bank. We find that withdrawals at one bank trigger withdrawals at another bank by increasing players' beliefs that other depositors in their own bank will withdraw, making them more likely to withdraw as well. Importantly though, observed withdrawals affect depositors' beliefs, and are thus contagious, only when depositors know that there are economic linkages between their bank and the observed bank.
Keywords: D81; G21; G28; 330; bank runs; Contagion; systemic risk